Detection and molecular characterization of Blastocystis sp., Enterocytozoon bieneusi and Giardia duodenalis in asymptomatic animals in southeastern Iran - Hatam-Nahavandi, Kareem; Mohammad Rahimi, Hanieh; Rezaeian, Mostafa; Ahmadpour, Ehsan; Badri, Milad; Mirjalali, Hamed (Scientific reports, 2025)
Domestic animals can harbor a variety of enteric unicellular eukaryotic parasites (EUEP) with zoonotic potential that pose risks to human health. The aim of this study was to evaluate the occurrence and genetic diversity of EUEP of zoonotic relevance in domestic animals in Iran. Faecal samples were collected from cattle, sheep, camels, goats, donkeys, horse, and dogs. A real-time PCR was performed to detect the parasites, followed by sequence-based genotyping analyses on isolates that tested positive for Enterocytozoon bieneusi , Giardia duodenalis , and Blastocystis sp.. Overall, 53 out of 200 faecal samples (26.5%, 95% CI 20.5–33.2) were positive for one or more EUEP. Enterocytozoon bieneusi was found in 23.8%, 12.0%, 26.1%, and 13.3% of cattle, sheep, goats, and camels, respectively. Giardia duodenalis was identified in 19.3% of cattle and 6.7% of camels. Blastocystis sp. was detected in 5.7% of cattle and 16.7% of camels. Enterocytozoon bieneusi genotypes macaque1, J, BEB6, and CHG3 were identified in 3.7% (1/27), 3.7% (1/27), 44.4% (12/27), and 48.2% (13/27) of the isolates, respectively. Giardia duodenalis assemblage B and Blastocystis subtype 10 were identified in one cattle and one camel isolate, respectively. These findings suggest that domestic animals could serve as potential reservoirs for EUEP of zoonotic relevance and might play a significant role in transmitting these parasites to humans and other animals.